2022
DOI: 10.3390/jcm11236993
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Machine Learning Techniques to Forecast Chronic Total Occlusion before Coronary Angiography

Abstract: Background: Chronic total occlusion (CTO) remains the most challenging procedure in coronary artery disease (CAD) for interventional cardiology. Although some clinical risk factors for CAD have been identified, there is no personalized prognosis test available to confidently identify patients at high or low risk for CTO CAD. This investigation aimed to use a machine learning algorithm for clinical features from clinical routine to develop a precision medicine tool to predict CTO before CAG. Methods: Data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In our study, we found that the occurrence of CTO in patients was linked to male sex and lipid metabolism, which is consistent with prior studies ( 16 , 17 ). However, it is noteworthy that predictive model developed using LASSO regression analysis included non-HDL rather than LDL, which has long been considered a secondary target of lipid-lowering therapy in CAD or in patients at high risk ( 18 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we found that the occurrence of CTO in patients was linked to male sex and lipid metabolism, which is consistent with prior studies ( 16 , 17 ). However, it is noteworthy that predictive model developed using LASSO regression analysis included non-HDL rather than LDL, which has long been considered a secondary target of lipid-lowering therapy in CAD or in patients at high risk ( 18 ).…”
Section: Discussionsupporting
confidence: 93%
“…In our previous work, we developed a nomogram using logistic regression analysis ( 8 ). However, we found that LASSO regression analysis is a superior method to univariate logistic regression analysis as it accounts for multicollinearity between variables.…”
Section: Discussionmentioning
confidence: 99%
“…Previous predictive models have incorporated various traditional clinical indicators, including general clinical characteristics and laboratory parameters, to assess the severity and prognosis of CTO patients 31 , 32 . Their application in clinical practice remains challenging, because some models omit crucial MPI variables.…”
Section: Discussionmentioning
confidence: 99%
“…5 Through analyses of CTO data embedded in clinical characteristics, along with the use of machine learning algorithms, early and accurate identification of CTO may lead to more effective treatment and better patient outcomes. 6 Here, we conducted a risk factor analysis and constructed three models to predict CTO risk based on clinical and demographic characteristics, as well as biochemical parameters and echocardiography findings. Computational analysis revealed that these models can provide clinically relevant predictions of CTO risk, highlighting the emerging opportunity to meet an important need in this field.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Through analyses of CTO data embedded in clinical characteristics, along with the use of machine learning algorithms, early and accurate identification of CTO may lead to more effective treatment and better patient outcomes. 6 …”
Section: Introductionmentioning
confidence: 99%